Interview mit dem Schleier - Meyer, Eva (My University, 2017)
Interviewing means mutually seeing one another. When the gaze hits a veil, it is doubled and broken in another gaze that also sees and is seen, although not simultaneously. Instead of registering objectively, we speak in a room where the lines of flight seem to go dark in the beyond, from where they come back into the world authorized. But the veil is a blind spot between these two poles, confusing the division into the profane and the sacred. Through stories coming from elsewhere and colonized by its own mythology, it circulates in the informational space of an opacity that indirectly relates flight and line to one another, inventing new ways to use media to work out difference and to move what is inadequate. Perhaps this attests to a lack in the power of imagination and need not signify anything unreal. Deliberately and systematically indirect, we look the complexity of the world in the face.
Keywords: 700 Künste, Bildende und angewandte Kunst; 300 Sozialwissenschaften